Investigation on Sanitational Aspects (Microbiological) of Prawn Processing Factories - Gopalakrishnan, T S; Chaudhuri, D R (Fishery Technology, 1965)
Investigation on Sanitational Aspects (Microbiological) of Prawn Processing Factories